PELATIHAN PENULISAN PRESS RELEASE DENGAN METODE KOMUNIKASI, INFORMASI, DAN EDUKASI GUNA MEMPERSIAPKAN PUBLIC RELATIONS SPECIALIST - Zuhri, Al; Salma, Cut Reski; Ditya, Dyta Dinda; Mulyani, Windi; Sarfika, Desi; Sahputra, Adi; Handayani, Mersi; Kania, Riza; Zahara, Rita (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2024)
Press releases are a good skill to have, so that the participation of SMKN 1 Meulaboh students in this training activity has great potential to provide significant benefits for themselves, school, and surrounding community. By gaining skills in releases, students are able to analyze, interpret, and write information appropriately. In the service process, team used Communication, Information, Education method using pre-test and post-test instruments. Pre-test was used to see the students' initial level of knowledge and understanding of the material before the service was given. The result was that 5 out of 23 students only succeeded in filling in 4 of the 8 questions given regarding the press release. At this stage, the percentage of students' knowledge and understanding of releases is still 50%. Meanwhile, post-test is an instrument for final assessment and evaluation after service is carried out. The results obtained from the post-test were that 18 out of 23 students succeeded in understanding 75% of the material that had been taught. This shows that the majority of students succeeded in understanding the material taught in community service.Then the students were also able to produce a release product, but it was still not optimal and a basic level.